MENGANALISIS PEMAHAMAN ORANG MUDA KATOLIK TENTANG POLITIK PRAKTIS DI STASI STA. MARIA GORETI ARAMENGI PAROKI SALIB SUCI HOELEA KEUSKUPAN LARANTUKA - Robbi, Chomarius; Dau, Yoseph Lodowik Deki; Abatan, Yofince; Tukan, Antonius I. Nggino; Masan, Valentinus Kopong (STIPAS Keuskupan Agung Kupang, 2024)
This research aims to analyze the understanding of young Catholics about practical politics at Stasi Sta. Maria Goreti Aramengi, Hoelea Holy Cross Parish, Larantuka Diocese. The research method used is a qualitative method with a focus on content analysis to understand the complexity of the phenomenon being studied. The research results show that the majority of young Catholics in this station have a good understanding of practical politics. Supporting factors include Church social teaching, Catholic religious education, spiritual leadership and formation, collaborative discussions, opportunities for involvement, and spiritual formation. Meanwhile, inhibiting factors include a lack of understanding of the Church's social teachings, the influence of secular culture, indifference to politics, lack of access to information and education, and the perception of politics as controversial. Efforts to increase practical political understanding include open discussion, education and spiritual formation.